2012
DOI: 10.1111/j.1476-5381.2011.01664.x
|View full text |Cite
|
Sign up to set email alerts
|

TM‐25659 enhances osteogenic differentiation and suppresses adipogenic differentiation by modulating the transcriptional co‐activator TAZ

Abstract: BACKGROUND AND PURPOSEThe transcriptional co-activator with PDZ-binding motif (TAZ) is characterized as a transcriptional modulator of mesenchymal stem cell differentiation into osteoblasts and adipocytes. Moreover, increased TAZ activity in the nucleus enhances osteoblast differentiation and suppresses adipocyte development by interacting with runt-related transcription factor 2 (RUNX2) and PPARg, respectively. Therefore, it would be of interest to identify low MW compounds that modulate nuclear TAZ activity.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
30
0
2

Year Published

2013
2013
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(35 citation statements)
references
References 49 publications
(60 reference statements)
3
30
0
2
Order By: Relevance
“…The osteogenic and antiadipogenic effects of kaempferol, a dietary flavonoid, depend on TAZ, supporting the notion that TAZ can be a therapeutic target in osteoporosis and obesity (55). Accordingly, the TAZ activator TM-25659 has been proposed to be beneficial in the control of osteoporosis and obesity (56). However, in the treatment of osteoporosis, the patients are females after menopause and relatively young.…”
Section: Discussionmentioning
confidence: 99%
“…The osteogenic and antiadipogenic effects of kaempferol, a dietary flavonoid, depend on TAZ, supporting the notion that TAZ can be a therapeutic target in osteoporosis and obesity (55). Accordingly, the TAZ activator TM-25659 has been proposed to be beneficial in the control of osteoporosis and obesity (56). However, in the treatment of osteoporosis, the patients are females after menopause and relatively young.…”
Section: Discussionmentioning
confidence: 99%
“…Although 2.3 kb Col 1 promoter drives transgenes specifically in mature osteoblasts [36], previous studies demonstrated that overexpression of Runx2 driven by 2.3 kb Col 1 promoter led to increased bone resorption phenotypes, primarily due to increased RANKL expression [37], [38]. A recent study also showed that treatment with small molecule that activates TAZ could protect ovariectomy-induced bone loss in vivo [39]. However, in our study, the RANKL/OPG expression levels in calvaria cells from Col.1-TAZ mice were not significantly different from those from WT mice.…”
Section: Discussionmentioning
confidence: 99%
“…Jang et al . expressed GFP‐TAZ in COS‐7 cells and identified novel TAZ activators . In this study, we expressed GFP‐TAZ in U2OS cells and applied small chemical compounds to these cells.…”
Section: Discussionmentioning
confidence: 99%
“…(44) Jang et al expressed GFP-TAZ in COS-7 cells and identified novel TAZ activators. (45) In this study, we expressed GFP-TAZ in U2OS cells and applied small chemical compounds to these cells. We aimed in this study to validate that this cell-based assay provides the compounds that inhibit TAZ through the Hippo pathway.…”
Section: Discussionmentioning
confidence: 99%